FAKTOR-FAKTOR PENDORONG DAN PENGHAMBAT IMPLEMENTASI INOVASI SEKTOR PUBLIK DI KOTA PADANG PANJANG - Barsei, Adhityo Nugraha (Jurnal Ilmu Administrasi Negara (JUAN), 2022)
The COVID-19 pandemic has had an impact on access to public services. The Padang Panjang City Government, in collaboration with the State Administration Institute, held an Innovation Laboratory activity. This activity aims to ensure that the Padang Panjang City Government can continue to provide services to the community despite the pandemic. However, the Innovation Laboratory activities not running well. This study aims to analyze the factors driving and inhibiting the implementation of innovation in the city of Padang Panjang. This research is descriptive qualitative research. The research was at the Office of the Planning, Research, and Development Agency (Bappedalitbang) of Padang Panjang City. The researcher collects data through in-depth interviews, documentation, and literature studies. informan was chosen by using a purposive sampling technique, namely innovators who have produced innovations from each OPD of Padang Panjang City. The data analysis technique uses selecting, compiling, and drawing conclusions. This study's results found the driving factors, namely the support of the Regional Head, align with regional mission, clear SOPs / technical guidelines, knowledge transfer of innovation, and stakeholder involvement. Meanwhile, the limited number of innovation managers, the limited ability of innovation managers, and the mutation/rotation of employees who are competent towards innovation become barriers factors.